Research on Control Strategy of Voltage Source Full Power Wind Power Converter - ZHOU Wang; HE Xi; LI Bingzhang; PENG Yun; CHEN Long; DAI Xixi (Kongzhi Yu Xinxi Jishu)
In the operating environment of power system with weak grid characteristics, the traditional current source converter control mode is prone to vibration, which increases the crossing difficulty and off-grid probability of wind turbines. Based on virtual synchronous generator (VSG) technology, a novel control strategy of voltage source converter is designed in this paper, and the voltage source converter control mode and current source converter control mode are studied. Under normal grid-connected operation conditions, voltage source converter control mode is adopted. Active power control increases active power compensation through VSG, and reactive current is injected into the front end of reactive power control. Under start-stop and high & low-voltage ride-through conditions, the current source converter control mode is adopted. The control strategy combines the advantages of voltage source converter control mode and the current source converter control mode. It has not only the frequency support characteristics, but also the fast active and reactive power response capability. The simulation and prototype experiments on the grid-connection process, active and reactive power response and high & low-voltage ride-through process of the full-power wind power converter are carried out. The results show that the proposed control scheme can achieve good control effect under each operating condition of the wind power converter, so that the wind power units have good steady-state and dynamic performance, and can well adapt to the demands of new energy grid-connection.